Designing a Parent Training Model to Prevent Cyber Space Risks in Students - Seyed Majid Karimi; Seyed Mohammadbagher Jafari; Gholamreza Sharifi Rad; Ali Akbar Khoshgoftar Moghadam (Iranian Journal of Educational Research)
Objective: A principal challenge associated with technological advancement pertains to the cultural and societal detriments that ensue as a consequence. The advent of the Internet and social networking platforms, coupled with an increase in individual liberties, has enabled swift access to a plethora of diverse and frequently unethical content available online. Given that the family unit serves as the cornerstone of all other social institutions and that individuals' mental health is largely cultivated within this context, the implementation of parental training programs is pivotal in regulating children's engagement with this digital environment. The objective of this research is to devise a parental education framework aimed at mitigating the adverse effects of virtual spaces on students. Methods: Employing a thematic analysis approach, semi-structured interviews were utilized as the primary means of data collection. Through the application of grounded theory methodology, the data acquired from interviews with eleven experts and professionals within the domains of family dynamics and education were systematically coded and examined through three distinct phases: open coding, axial coding, and selective coding. Results: The findings elucidated six principal categories within a paradigm model that encompasses comprehensive management, analysis, design, preparation, implementation, and evaluation. The results indicate that parental education, guidance and counseling support, the promotion of safe conduct within family units, the encouragement of enhanced family communication, the provision of supportive resources, the augmentation of parental awareness, the fostering of parental collaboration with educational institutions, and the encouragement and facilitation of parental cooperation with schools are all essential elements Conclusions: The instruction of technological competencies and the establishment of mutual agreements concerning the safe and responsible utilization of virtual environments may function as efficacious strategies for preventing the detrimental impacts of virtual spaces on students.